Hubungan Asupan Natrium Dengan Kejadian Osteoporosis Pada Lansia Pasien Rawat Jalan di Rumah Sakit Ortopedi Prof. Dr. R. Soeharso Surakarta - Liswandayu, Amalia, Elida Soviana, S.Gz., M.Gizi, Siti Zulaekah, A., M.Si (2016)
Background : Elderly cause physical deterioration that cause osteoporosis. Osteoporosis is condition in which bone density decrease. Calcium is one of the factors that influence the incidence of osteoporosis because calcium is one of minerals that contribute to the bone formation. High sodium intake will affect the calcium metabolism and increase the calcium excretions in urine. Objective : The purpose of this research was to know the relationship between sodium intake with the occurrence of osteoporosis in elderly patients outpatients at RSO. Prof. Dr. R. Soeharso Surakarta. Research Method : The research is observational method with cross-sectional approach. The number of subjects was 22 patients obtained by consecutive sampling who met the criteria of inclusion and exclusion. Adequate intake level data retrieval sodium trough semi-quantitative FFQ. Data of osteoporosis obtained from Bone Mineral Density (BMD) examination. Statistical tests used the Rank Spearman. Result : The result showed 72.7% had less sodium intake with average 435.7±329.7 mg. The subject that occur osteoporosis is 54.5% and did not occur osteoporosis is 45.5%. The Rank Spearman test show the value of p=0,557. Conclusion : There is no relationship between sodium intake with the occurrence of osteoporosis. Key Words : osteoporosis, elderly, sodium intake